Estrategia publicitaria para la promoción de la licorería “La Celestial” en plataformas digitales - Rodriguez Torres, Jorge Luis (2024)
The present research aims to study an advertising strategy to promote the liquor store on digital platforms. The purpose is to reach a wider audience in the area and generate presence in social networks, as it is currently an effective way to increase sales and publicize the products of an establishment. The study will focus on identifying the most appropriate digital platforms for the promotion of the liquor store, as well as developing an effective advertising strategy to reach the target audience. The implementation of an advertising strategy on digital platforms will allow the liquor store to increase its visibility, attract new customers and strengthen its presence in the local market. In addition, it is expected that this strategy will contribute to boost sales and position the liquor store as a reference establishment in the Celica canton. The liquor store "La Celestial", located in the canton of Celica, province of Loja, has faced difficulties in the promotion and diffusion of its products due to the competition in the area, which has resulted in a decrease in sales in the last year.